2016
DOI: 10.1097/mlr.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health, Cost-related Nonadherence, and Cost-reducing Behaviors Among Adults With Diabetes

Abstract: Background Cost-related non-adherence (CRN) is prevalent among individuals with diabetes and can have significant negative health consequences. We examined health and non-health-related pressures and the use of cost-reducing strategies among the U.S. adult population with and without diabetes that may impact CRN. Methods Data from the 2013 wave of National Health Interview Survey (n=34,557) were used to identify the independent impact of perceived financial stress, financial insecurity with healthcare, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 24 publications
6
95
0
Order By: Relevance
“…Individuals living in socioeconomically disadvantaged circumstances are at increased risk of developing chronic medical conditions, face greater barriers to successful disease management, and experience higher rates of both emergency department utilization and inpatient hospital admissions. [1][2][3][4][5][6] Recognizing the importance of social determinants of health (SDH) to health outcomes, utilization, and costs, the National Academy of Medicine, Centers for Disease Control and Prevention, and Centers for Medicare & Medicaid Services have all called for evidencebased initiatives to better screen for and address SDHs in clinical settings. [7][8][9] While growing evidence informs instruments used to screen for SDH, 10 -16 little is known about current screening practices for SDH in clinical settings.…”
mentioning
confidence: 99%
“…Individuals living in socioeconomically disadvantaged circumstances are at increased risk of developing chronic medical conditions, face greater barriers to successful disease management, and experience higher rates of both emergency department utilization and inpatient hospital admissions. [1][2][3][4][5][6] Recognizing the importance of social determinants of health (SDH) to health outcomes, utilization, and costs, the National Academy of Medicine, Centers for Disease Control and Prevention, and Centers for Medicare & Medicaid Services have all called for evidencebased initiatives to better screen for and address SDHs in clinical settings. [7][8][9] While growing evidence informs instruments used to screen for SDH, 10 -16 little is known about current screening practices for SDH in clinical settings.…”
mentioning
confidence: 99%
“…Furthermore, there are resources available for the inclusion of standardized sociodemographic variables in electronic medical records to facilitate the measurement of health inequities as well as the impact of interventions designed to reduce those inequities (61-63). Social determinants of health are not always recognized and often go undiscussed in the clinical encounter (57). A study by Piette et al (64) found that among patients with chronic illnesses, two-thirds of those who reported not taking medications as prescribed due to cost never shared this with their physician.…”
Section: Strategies For System-level Improvementmentioning
confidence: 99%
“…A study by Piette et al (64) found that among patients with chronic illnesses, two-thirds of those who reported not taking medications as prescribed due to cost never shared this with their physician. In a more recent study using data from the National Health Interview Survey (NHIS), Patel et al (57) found that half of adults with diabetes reported financial stress and one-fifth reported food insecurity (FI). Creating systems-level mechanisms to screen for social determinants of health may help overcome structural barriers and communication gaps between patients and providers (57).…”
Section: Strategies For System-level Improvementmentioning
confidence: 99%
See 2 more Smart Citations